2016
DOI: 10.1007/s11096-016-0304-7
|View full text |Cite
|
Sign up to set email alerts
|

Resource use and cost of care with biologicals in Crohn’s disease in South Africa: a retrospective analysis from a payer perspective

Abstract: Background Crohn's disease is a relapsing remitting inflammatory disease of the gastrointestinal tract. Treatment may require expensive biological therapy in severe patients. Affordability of the high cost anti-TNF-α agents has raised concern although evidence suggests cost-offsets can be achieved. There is little information on the resource utilisation of Crohn's patients in low and middle income countries. Objective The objective of this study is to investigate the resource utilisation and costs associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…However, biologic initiation was associated with an increase in pharmacy costs by 40% and total costs by 6%. Similarly, other studies in various healthcare systems have associated biologic initiation with a reduction in inpatient and outpatient visits and their associated costs; however, an increase in pharmacy costs, most likely due to biologic prescriptions, resulted in greater total direct costs compared with pre-biologic expenses [30][31][32]. Although the present study did not distinguish between biologic and other drug-related costs, Saito et al [18] analyzed patient data (2013-2016) from the JMDC database and reported the total CDrelated costs to be ¥7,139,604,830, with anti-TNFα agents accounting for 59.5% of the total…”
Section: Plos Onementioning
confidence: 96%
“…However, biologic initiation was associated with an increase in pharmacy costs by 40% and total costs by 6%. Similarly, other studies in various healthcare systems have associated biologic initiation with a reduction in inpatient and outpatient visits and their associated costs; however, an increase in pharmacy costs, most likely due to biologic prescriptions, resulted in greater total direct costs compared with pre-biologic expenses [30][31][32]. Although the present study did not distinguish between biologic and other drug-related costs, Saito et al [18] analyzed patient data (2013-2016) from the JMDC database and reported the total CDrelated costs to be ¥7,139,604,830, with anti-TNFα agents accounting for 59.5% of the total…”
Section: Plos Onementioning
confidence: 96%
“…[3] Data from a variety of studies indicates that CD is associated with substantial direct and in-direct costs across patients’ lifespan. [4,5] Symptoms of active CD, such as diarrhea and abdominal pain, have been shown to impact health related quality of life substantially in large multinational studies. [6,7]…”
Section: Introductionmentioning
confidence: 99%